Determination of fipronil and its metabolites in edible oil by pollen based solid-phase extraction combined with gas chromatography-electron capture detection. (30th May 2022) - Zhou, Yi-Lian; Yue, Shi-Wen; Cheng, Bing-Wei; Zhao, Qin
Highlights: A new method for the determination of fipronil and its three metabolites in edible oils was developed by pollen based SPE. Pollen sorbent showed well extraction performance towards fipronil and its three metabolites. Pine pollen grains are more economic and can be obtained from renewable source. The nature pine pollen grains have great application potential in sample preparation. Abstract: In this study, a convenient and economic method for the determination of fipronil and its three metabolites in edible oil was developed based on pollen grain solid-phase extraction (SPE). As a natural material, pollen grains exhibit well absorption capacity for some polar compounds due to their special functional structures. Their stable composition and appropriate particle size also make them suitable for SPE. In the present study, natural pine pollen grains without broken wall were used as sorbent for selective isolation and enrichment of fipronil and its three metabolites from edible oils based on hydrogen bond interaction. Several parameters influencing the extraction recoveries were investigated. By coupling with gas chromatography-electron capture detection (GC-ECD), a new method for analysis of fipronil and its metabolites in edible oils was established. The linearity range was 2–200 ng/g with correlation coefficient R 2 more than 0.999. The recoveries in edible oils at three spiked concentrations were in the range of 80.1–96.0% with the RSDs less than 10.6% (intra-day) and 11.5% (inter-day). The limit of detection (LOD) for four target analytes were in the range of 0.2–0.6 ng/g, which was comparable to the previous reported methods. Finally, the established method was successfully applied to detect fipronil and its metabolites in several oil samples with different brands from local market.